The problem of activity specifications - Vladimirovich Baranov, Gennady (Opción, 2019)
The present research aimed to theoretically justify an onto-metaphysical hypothesis about the essence of activity in an attributive condition of antikhaosny life implementation. Ontologic approach was applied as the leading method providing the egoism knowledge of an object, abstracting from valuable criteria and sociocultural effects. The present paper presents justification of the activity concept in value of attributive representation of life perfection as the self-implementation according to condition life an autonomous definiteness by means of antikhaosny transformation of internal and external factors in the environment.